Che Guevara a revolutionary life - Anderson, Jon Lee. (Blackstone, 2008)
This New York Times ?Notable Book of the Year? is the definitive biography on Che Guevara, whose epic dream was to end poverty and injustice in Latin America through armed revolution. Anderson?s biography traces Che?s extraordinary life, from his comfortable Argentine upbringing to the Cuban revolution, from the halls of power in Castro?s government to his failed campaign in the Congo and assassination in the Bolivian jungle.
Keywords: Guevara, Che, 1928-1967.